Addressing the Issues and Approaches to Reduce Youth Smoking in Indonesia - Radian Ilmaskal; Rinaldi Daswito (Journal of Health Sciences and Epidemiology, 2023)
This article examines prominent concerns regarding adolescent smoking in Indonesia and investigates diverse strategies targeted at mitigating this public health issue.   Indonesia is confronted with an escalating epidemic of tobacco consumption among young people, which is worsened by inadequate legislation and assertive marketing strategies employed by tobacco corporations. This article addresses the difficulties associated with the cultural acceptability of smoking, the restricted availability of quitting resources, and the lack of comprehensive anti-smoking programs. The paper emphasizes the significance of enhancing more stringent tobacco control legislation and implementing cross-sector collaboration activities specifically designed for the Indonesian context to address the problem of individuals who start smoking for the first time.   This article emphasizes the importance of protecting the health and future of Indonesia's youth population by tackling these challenges and applying different prevention techniques.